Stereotactic body radiation therapy for the primary treatment of localized prostate cancer - Oliai, Caspian (Springer-Verlag, 2012)
OBJECTIVE: The low alpha/beta ratio of prostate cancer suggests that hypofractionated schemes of dose-escalated radiotherapy should be advantageous. We report our experience using stereotactic body radiation therapy (SBRT) for the primary treatment of prostate cancer to assess efficacy and toxicity. METHODS: From 2007 to 2010, 70 patients (51 % low risk, 31 % intermediate risk, and 17 % high risk) with localized prostate cancer were treated with SBRT using the CyberKnife system. One-third of patients received androgen deprivation therapy. Doses of 37.5 Gy (n = 29), 36.25 Gy (n = 36), and 35 Gy (n = 5) were administered in five fractions and analyzed as high dose (37.5 Gy) vs. low dose (36.25 and 35 Gy). RESULTS: At a median 27 and 37 months follow-up, the low and high dose groups' median PSA nadir to date was 0.3 and 0.2 ng/ml, respectively. The 3-year freedom from biochemical failure (FFBF) was 100 %, 95.0 % and 77.1 % for the low-, intermediate- and high-risk patients. A dose response was observed in intermediate- and high-risk patients with 72 % vs. 100 % 3-year FFBF for the low and high dose groups, respectively (p = 0.0363). Grade III genitourinary toxicities included 4 % acute and 3 % late (all high dose). Potency was preserved in 83 % of hormone naïve patients. CONCLUSION: CyberKnife dose escalated SBRT for low-, intermediate- and high-risk prostate cancer exhibits favorable efficacy with acceptable toxicity.